Temperature Effects on Mobile Charges in Thermopiezoelectric Semiconductor Plates - Qu, Yilin; Jin, Feng; Yang, Jiashi (International journal of applied mechanics, 2021)
We study the temperature effects on mobile charges in a thermopiezoelectric semiconductor plate through pyroelectric and thermoelastic couplings. The macroscopic theory of thermopiezoelectric semiconductors is used. A set of two-dimensional (2D) equations is derived for extension and bending with shear deformation of the plate. A few solutions are obtained. Numerical results show that the distribution of the mobile charges in the plate can be manipulated by the temperature field. In the case of temperature-induced uniform extension, a combination of physical parameters is identified which characterizes the strength of the coupling between the temperature field and the mobile charge distribution. The results obtained are fundamental to piezotronic devices involving temperature effects.